A review article of multi-band, multi-mode microstrip filters for RF, WLAN, WiMAX, and wireless communication by using stepped impedance resonator (SIR) - Alkhafaji, Mohammed K.; Sahbudin, Ratna Kalos Zakiah (Universiti Putra Malaysia Press, 2017)
Filters are the basic part in wired, and wireless telecommunications and radar system circuits and they play an important role in determining the cost and performance of a system. The increasing demand for high performance in the fields of RF, WLAN, WiMAX and other wireless communications led to the great revolution in the advancement of the development of a compact microstrip resonator filter design. All these have made a vital contribution to both the required performance specifications for filters and other commercial requirements in terms of low cost, large storage capacity and high-speed performance. This review paper presents several design examples for multi-band, multi - mode microstrip filter resonators to satisfy RF, WLAN, WiMAX, UWB and other wireless communication frequency bands. To analyse the resonant frequencies odd - mode and even -modes can be used for the symmetrical structure. In general, the multi-mode resonators can be designed by using different methods like cross-coupling resonators Structure, and the allocation of the fundamental resonant frequencies of the resonator as stated by the Chebyshev's insertion loss function.